2022
DOI: 10.37467/revtechno.v11.4468
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo de habilidades blandas e intención emprendedora en los estudiantes universitarios

Abstract: La educación en emprendimiento ha experimentado un importante auge en los últimos años, siendo imprescindible que las universidades promuevan una cultura emprendedora para optimizar la empleabilidad de sus estudiantes. Este trabajo pretende estudiar el impacto de la formación en emprendimiento sobre las habilidades blandas y la actitud emprendedora de dos grupos de estudiantes: grupo de control (área de Ciencias Sociales) y grupo experimental (área de Ciencias de la Salud), desarrollando planes de empresa. Los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Research on entrepreneurial management has been mainly related to the business sphere (Long et al, 2021;Ratten et al, 2021;Singh et al, 2022;Pallathadka et al, 2023) highlighting it as an essential element in the concretization of the actions raised, in the case of entrepreneurial management as a social entrepreneurship competence studies are scarce (Bonesso et al, 2018;Okolie et al, 2021;Cruz-Sandoval et al, 2022;Parejo et al, 2022;Romero and Nalangan, 2023) in particular, no studies were identified that relate entrepreneurial management to other variables that can explain the profile of social innovation in students, The literature on the subject highlights that entrepreneurial management is one of the elements in education to which less importance has been given and that this could have repercussions on the lack of confidence to undertake social entrepreneurship and thus to carry out actions that generate a social impact, so it is necessary to develop educational programs to promote entrepreneurial skills in the economic, social or technological fields (Ahmed et al, 2020;Jena, 2020;Aledo Ruiz, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Research on entrepreneurial management has been mainly related to the business sphere (Long et al, 2021;Ratten et al, 2021;Singh et al, 2022;Pallathadka et al, 2023) highlighting it as an essential element in the concretization of the actions raised, in the case of entrepreneurial management as a social entrepreneurship competence studies are scarce (Bonesso et al, 2018;Okolie et al, 2021;Cruz-Sandoval et al, 2022;Parejo et al, 2022;Romero and Nalangan, 2023) in particular, no studies were identified that relate entrepreneurial management to other variables that can explain the profile of social innovation in students, The literature on the subject highlights that entrepreneurial management is one of the elements in education to which less importance has been given and that this could have repercussions on the lack of confidence to undertake social entrepreneurship and thus to carry out actions that generate a social impact, so it is necessary to develop educational programs to promote entrepreneurial skills in the economic, social or technological fields (Ahmed et al, 2020;Jena, 2020;Aledo Ruiz, 2022).…”
Section: Introductionmentioning
confidence: 99%